Respuesta :

Answer:

k(3) is 7 and f(h(15)) is 43

Step-by-step explanation:

(a).

[tex]{ \sf{k(x) = h(x) + g(x)}} \\ { \sf{k(x) = (3 \sqrt{x + 1}) + ( - {x}^{2} + 3x + 1) }} \\ { \sf{k(x) = (3 \sqrt{3 + 1} ) + ( - {3}^{2} + 3(3) + 1) }} \\ { \sf{k(x) = 6 + 1}} \\ { \sf{k(x) = 7}}[/tex]

b).

[tex]{ \sf{f(h(x)) = 4(3 \sqrt{x + 1}) - 5 }} \\ { \sf{f(h(15)) = 4(3 \sqrt{15 + 1}) - 5 }} \\ { \sf{f(h(15)) = 4(3 \sqrt{16} ) - 5}} \\ { \sf{f(h(15)) = 48 - 5}} \\ { \sf{f(h(15)) = 43}}[/tex]

ACCESS MORE
EDU ACCESS